Solusi Cerdas dalam Berinvestasi - Hotniati Simamora (LPPM Universitas Widya Dharma Pontianak, 2022)
The rise of fraud in times of a pandemic has taken many victims. Many people have lost their jobs. Many companies limit productivity, so many employees are laid off. Situations that just stay at home limit the room for movement. We must take advantage of this difficult situation to continue to be creative. Many of these people use technology to continue working. With computer facilities, sitting comfortably for hours and looking for information through sosial media, news, lifestyle, creative content that affects the mindset and mentality of others. Opportunities are created, dreams are sold through enticing information, how to get as much money and profit as possible. Many fantastic investments, offering great returns. Many people compete to trade without thinking logically and critically. The vigilance fades with the level of profit dreamed of. Yes, we have uncertainty. When we face the Covid-19 pandemic, there are things that we do not expect. Fraudulent investment fraud, unreasonable trading is still rife recently. The action is carried out both online and offline. For that, we should always be vigilant and recognize the characteristics of fraudulent investments. So that we are not deceived, complacent and fall into it. Several fraudulent investment scams have been uncovered and a lot of evidence has been shared on sosial media. Usually fraudulent investments offer a large and lucrative profit. That way, the victims will be more interested and invest without thinking. However, we will not get profits, but we will actually get losses if we use investments that are not registered and under the supervision of the Financial Services Authority (OJK).Keywords: lifestyle, investment, financial strategy